Synthesis of Novel Bacterial Cellulose Based Silver-Metal Organic Frameworks (BC@Ag-MOF) as Antibacterial Wound Healing - Puspitasari, Nathania; Arief, David; Ismadji, Suryadi; Saraswaty, Vienna; Santoso, Shella Permatasari; Retnoningtyas, Ery Susiany; Putro, Jindrayani Nyoo; Gunarto, Chintya (Fine Chemical Engineering, 2023)
Bacterial Cellulose (BC) is a polymer derived from the bacterium Komagataeibacter xylinus with great potential for biomedical applications due to its high biocompatibility and biodegradability. In addition, the polymer is naturally biosynthesized by bacteria as hydrogels which can be used as optimal substrates for wound healing. However, the drawback of BC is the absence of antibacterial properties. Nowadays, some infections become more prevalent and harder to treat because of antimicrobial resistance, therefore, it is necessary to develop a strategy for modifying BC as wound healing that provides protection against bacterial contamination. In this work, silver-based Metal Organic Frameworks (MOFs) were immobilized into Bacterial Cellulose (BC). MOFs are porous coordination materials consisting of metal ions and multidentate organic ligands that have the potential as a matrix for metal ions due to their ability to gradually release metal ions. The structure and morphology of BC@Ag-MOF were successfully confirmed by Fourier-Transform Infrared spectroscopy (FTIR) and Scanning Electron Microscope (SEM). Evidently, BC@Ag-MOF exhibited a higher silver content (63.19%) than BC@Ag without immobilization into MOF (48.46%). Therefore, it indicated that MOF has large pores for enhancing the capacity for silver ion absorption in BC. The modified BC has never been reported and achieved the highest antibacterial activity of 99.99% against Gram-negative bacteria Escherichia coli. Moreover, BC@Ag-MOF has a higher antibacterial efficiency of 97% compared to BC@Ag without matrix. This study expands the potential application of BC modification in the field of biological antibacterial. has never been reported and achieved the highest antibacterial activity of 99.99% against Gram-negative bacteria Escherichia coli. Moreover, BC@Ag-MOF has a higher antibacterial efficiency of 97% compared to BC@Ag without matrix. This study expands the potential application of BC modification in the field of biological antibacterial.